Pengaruh Pertumbuhan Ekonomi dan Penanaman Modal Dalam Negeri (PMDN) terhadap Pengangguran - Isra Nadia; Khairul Amri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This research aims to estimate the realization of economic growth and PMDN on unemployment which is operationalized as a predictor variable. The interest rate margin for economic growth, domestic investment and unemployment are operationalized as predictor variables. Apart from that, unemployment is also positioned as a moderating variable between economic growth and PMDN. The data used is panel data from 6 provinces in Sulawesi using annual data for the 2016-2020 period. The analysis models is using panel regression with a fixed effect approach. Research finds that economic growth has no effects on unemployment. And PMDN has a significant effect on unemployment.